2023
DOI: 10.3390/ijerph20054342
|View full text |Cite
|
Sign up to set email alerts
|

Poor Self-Rated Health and Associated Factors among Older Persons in Malaysia: A Population-Based Study

Abstract: Objective: This study aims to determine the prevalence of poor self-rated health (SRH) in Malaysia and its association with sociodemographic characteristics, lifestyle behavior, chronic diseases, depression, and functional limitations in activities of daily living (ADLs) among older persons. Design: Cross-sectional. Setting, participants, and outcome measures: We used data from the National Health and Morbidity Survey 2018, a nationwide community-based study. This study was conducted using a two-stage stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Our finding reported greater proportion of respondents with limited ADL reported poor-SRH than those without the limitations. This finding is supported by studies from different countries showing individuals who reported difficulties performing ADLs are more likely to report poor-SRH [ 65 70 ]. ADL limitations can impact an older adult’s overall quality of life and sense of well-being.…”
Section: Discussionsupporting
confidence: 62%
“…Our finding reported greater proportion of respondents with limited ADL reported poor-SRH than those without the limitations. This finding is supported by studies from different countries showing individuals who reported difficulties performing ADLs are more likely to report poor-SRH [ 65 70 ]. ADL limitations can impact an older adult’s overall quality of life and sense of well-being.…”
Section: Discussionsupporting
confidence: 62%